বঙ্গবন্ধু শেখ মুজিবকে ঘিরে কিছু ঘটনা ও বাংলাদেশ - মিয়া, এম.এ. ওয়াজেদ 1942-2009
Reminiscences of the major political events in Bangladesh, 1961-1992; includes contributions of Sheikh Mujibur Rahman, 1922-1975, former president.